2022
DOI: 10.7717/peerj.13184
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury-attributable mortality in critically ill patients with sepsis

Abstract: Background To assess whether acute kidney injury (AKI) is independently associated with hospital mortality in ICU patients with sepsis, and estimate the excess AKI-related mortality attributable to AKI. Methods We analyzed adult patients from two distinct retrospective critically ill cohorts: (1) Medical Information Mart for Intensive Care IV (MIMIC IV; n = 15,610) cohort and (2) Wenzhou (n = 1,341) cohort. AKI was defined by Kidney Disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, our study only focused on septic patients, which may account for the disparity in results. According to Wang Zhiyi’s research [ 26 ], the Medical Information Mart for Intensive Care (MIMIC) IV cohort, consisting of 15,610 patients, had an excess attributable mortality rate of 58.6% for AKI in critically ill patients with sepsis. In contrast, in the Wenzhou cohort, consisting of 1,341 patients, the excess attributable mortality was 44.6%.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study only focused on septic patients, which may account for the disparity in results. According to Wang Zhiyi’s research [ 26 ], the Medical Information Mart for Intensive Care (MIMIC) IV cohort, consisting of 15,610 patients, had an excess attributable mortality rate of 58.6% for AKI in critically ill patients with sepsis. In contrast, in the Wenzhou cohort, consisting of 1,341 patients, the excess attributable mortality was 44.6%.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the conclusions of several previous studies, in which deteriorated renal function was a crucial prognostic factor affecting mortality in patients with severe infections, including BSI. 23 25 Westgeest et al 9 conducted a multicenter retrospective cohort study and found that AKI development was highly associated with 30-day mortality in patients with S. aureus bacteremia. Moreover, patients with CRAB complex bacteremia had poor clinical outcomes when they had AKI.…”
Section: Discussionmentioning
confidence: 99%
“…These events are also known to cause structural renal damage and functional impairment, a syndrome known as acute kidney injury (AKI) 19 , 24 , 25 . AKI does not only increase the risk for chronic kidney disease but is also attributed to high morbidity, especially in patients with preexisting conditions 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%